2018
DOI: 10.1519/jsc.0000000000002868
|View full text |Cite
|
Sign up to set email alerts
|

Response Time and Effectiveness in Elite Greco-Roman Wrestlers Under Simulated Fight Conditions

Abstract: Gierczuk, D, Bujak, Z, Cieśliński, I, Lyakh, V, and Sadowski, J. Response time and effectiveness in elite Greco-Roman wrestlers under simulated fight conditions. J Strength Cond Res 32(12): 3442–3449, 2018—The purpose of the study was to determine changes in response time and its correlations with tactical and technical actions performed by Greco-Roman wrestlers in a fight. Twenty wrestlers aged 19–25 (21.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
2
27
1
Order By: Relevance
“…anthropometric measurements of wrestlers at various levels of competition [8,9], development of motor abilities [3,7,10], technical and tactical wrestling skills [3,11,12] or physical performance [3,10,11,13] in the novice-expert domain. These studies showed that anthropometric measurements [14,15], upper and lower body strength, anaerobic power, strength endurance [3,7,10,11,13,16], response time [17] and technical wrestling skills such as suplex throw, throw over the hip (head and arm) and rear takedown by front waistlock [12,16,18] differentiated successful and less successful wrestlers of both styles [12,16]. Surprisingly, a lot of researchers omitted other important components of sports preparation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…anthropometric measurements of wrestlers at various levels of competition [8,9], development of motor abilities [3,7,10], technical and tactical wrestling skills [3,11,12] or physical performance [3,10,11,13] in the novice-expert domain. These studies showed that anthropometric measurements [14,15], upper and lower body strength, anaerobic power, strength endurance [3,7,10,11,13,16], response time [17] and technical wrestling skills such as suplex throw, throw over the hip (head and arm) and rear takedown by front waistlock [12,16,18] differentiated successful and less successful wrestlers of both styles [12,16]. Surprisingly, a lot of researchers omitted other important components of sports preparation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers emphasize the high ratio between the indices of the motor reaction of athletes and the result of competitive matches in Greco-Roman wrestling [23]. Finalists and winners of elite competitions (as a rule) have a higher response time rate than wrestling athletes who lost the tournament [33]. Our data show the presence of high rates of response rate in the selection of an average of 60% of athletes.…”
Section: Pedagogics Psychologymentioning
confidence: 54%
“…The results of our previous studies and those of a number of authors have shown the advantage of highly skilled wrestlers over less skilled and less prepared athletes in a number of physical fitness key parameters: physical development [2,9,17], functional state [19,21,35], special work capacity [8,36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite different approaches, most works presented a disparate material characterizing certain aspects of wrestlers' fitness: physical development [1,[15][16][17], functional state [18][19][20][21], level of development of individual motor qualities [1,22,23].…”
Section: Introductionmentioning
confidence: 99%